2019
DOI: 10.1159/000496719
|View full text |Cite
|
Sign up to set email alerts
|

pH-Wert und mikrobielle Infektionen

Abstract: Ein durchgängig saurer pH-Wert im Stratum corneum ist ein wesentlicher Bestandteil des Schutzsystems der Haut, der eine feindliche Umgebung für die Besiedelung durch pathogene Mikroorganismen schafft. Doch diese Barriere kann bei gesunder und umso mehr bei geschädigter Haut durchbrochen werden. Mykosen, Windel-/Inkontinenz-assoziierte Dermatitis und Wundheilung sind Beispiele für Situationen, in denen durch veränderte Haut- oder Umgebungsbedingungen eine mikrobielle Infektion begünstigt wird. Pilze verfügen üb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[ 73 ] Hence, it is important to maintain the wound environment at an acidic state (pH < 6) for clearing pathogenic microbes in the infected wound beds. [ 74 ] Based on this, we aimed to conjugate boric acid (H 3 BO 3 ) with GFPDOPA at neutral and alkaline pH. In the oxidation state, DOPA forms bidentate complexation with boric acid (BA) and prevents the spontaneous autoxidation in an alkaline pH.…”
Section: Resultsmentioning
confidence: 99%
“…[ 73 ] Hence, it is important to maintain the wound environment at an acidic state (pH < 6) for clearing pathogenic microbes in the infected wound beds. [ 74 ] Based on this, we aimed to conjugate boric acid (H 3 BO 3 ) with GFPDOPA at neutral and alkaline pH. In the oxidation state, DOPA forms bidentate complexation with boric acid (BA) and prevents the spontaneous autoxidation in an alkaline pH.…”
Section: Resultsmentioning
confidence: 99%
“…The iodine-rich algae (e.g., Laminaria Japonica) can be used to constrain cellulite since iodine regulates the thyroid hormones' synthesis, which boosts lipolysis by facilitating the penetration of fatty acids into the mitochondria [192,271,272].…”
Section: Algae Metabolites In Anticellulite and Slimming Care Formula...mentioning
confidence: 99%
“…For example, the pH of skin wounds, especially chronic wounds, is often slightly alkaline (chronic wound pH ranges from 5.45 to 8.65 with an average of 7.42) and affects cell and subcellular functions, enzyme activity, protein conformation expression, and bacterial colonization. 46,47 A recent study on temperature indicated that a chronic wound bed (30.2-33.0 °C) is slightly lower in temperature than normal trunk skin (33.5-36.9 °C). 48 The standard smart category includes temperature-sensitive, pH/salt-sensitive, light-sensitive, electromagnetic electricitysensitive, and pressure-sensitive hydrogels (Fig.…”
Section: Smart Hydrogelmentioning
confidence: 99%